Tổng hợp và nghiên cứu hoạt tính xúc tác của hệ Cu/bentonit chống lớp cho phản ứng oxi hóa CO - Thu Thủy, Lương Thị; Cầm, Lê Minh (Vietnam Journal of Chemistry, 2016)
Montmorillonite clay was intercalated and pillared by polycation Al, then used as a support for copper and cerium oxides catalytic systems. The pillared bentonite as well as pillared bentonite supported-catalysts was characterized by means of XRD, SEM, BET and TGA. The prepared catalysts were tested for the oxidation process of CO. The pillared bentonite is proved to make a better support than parent clay since it can improve the CO conversion from 13 % over Ce-Cu/Bent-TC to 70 % over Ce-Cu/Bent-Al with the same amount of the active oxides. By introducing 2 % Ce (Ce-Cu/Bent-Al), a higher CO conversion was found at temperature as low as 250 oC in comparison to that over Cu/Bent-Al sample. In addition, the impregnation method had created a more active Ce than Ce adding direct into the intercalation solution, the catalyst not only showed its activity at a lower temperature but also gave a higher CO conversion. The catalyst was then tested for 3 times and showed a potential in reuse